2021
DOI: 10.1093/sleep/zsab072.113
|View full text |Cite
|
Sign up to set email alerts
|

114 Stability of Gut Microbiome Alpha Diversity During Combined Sleep Restriction and Circadian Misalignment

Abstract: Introduction Disturbed gut microbiome diversity has been associated with poor health outcomes and various disease states. We investigated the impact of combined sleep restriction (3h time in bed [TIB] sleep opportunities per day) and circadian misalignment (daytime sleep and nighttime wakefulness) on gut microbiome alpha diversity in healthy young individuals in a controlled laboratory setting. Methods Twenty healthy adults (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, the current results are consistent with those of Zhang et al (2017) , who showed that short-term sleep restriction did not significantly alter the OTU abundance, β diversity, and population shift of the gut microbiota in humans. In addition, the latest evidence has indicated that short-term sleep restriction and circadian misalignment do not appear to impair the stability of the alpha diversity of the human microbiome ( Withrow et al 2021 ). On the other hand, some researchers studied these relationships from a new perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current results are consistent with those of Zhang et al (2017) , who showed that short-term sleep restriction did not significantly alter the OTU abundance, β diversity, and population shift of the gut microbiota in humans. In addition, the latest evidence has indicated that short-term sleep restriction and circadian misalignment do not appear to impair the stability of the alpha diversity of the human microbiome ( Withrow et al 2021 ). On the other hand, some researchers studied these relationships from a new perspective.…”
Section: Discussionmentioning
confidence: 99%